Motion stabiliser - Ishak, Asnor Juraiza (Universiti Putra Malaysia Press, 2016)
Plasticity is the ability to change and adapt, especially the ability of the central nervous system to acquire alternative pathways for sensory perception or motor skills. It allows the recovery of motor skills after stroke and other neurological diseases. The repetitive locomotion training aims to activate spinal and supraspinal pattern generators in spinal cord injury patients.